Optimalisasi Lahan Pekarangan melalui Pengembangan Tanaman Jahe di Desa Pargarutan Dolok, Kabupaten Tapanuli Selatan - Siti Hardianti Wahyuni; Meiliana Friska; Surya Handayani; Jumaria Nasution; Sriwinaty Harahap (Jurnal INDONESIA RAYA (Pengabdian pada Masyarakat Bidang Sosial, Humaniora, Kesehatan, Ekonomi dan Umum), 2025)
This community service program aims to optimize the utilization of home gardens through the development of ginger (Zingiber officinale) cultivation in Pargarutan Dolok Village, South Tapanuli Regency. The activity was implemented in response to the low productivity of village home gardens, which are generally underutilized for economic purposes. The implementation method employed a participatory approach involving local residents directly through stages of socialization, training, demonstration plot establishment, technical assistance, and program sustainability evaluation. A total of 42 families actively participated out of 60 targeted households, with a plant growth success rate of 92%. The application of liquid organic fertilizer and botanical pesticides effectively increased the number of shoots and reduced the incidence of plant diseases. The social impact showed an 85% improvement in community awareness and skills in utilizing home gardens, along with the formation of the “Jahe Sejahtera Pargarutan” group as a collaborative business platform. Economically, the potential additional household income from 50 ginger polybags reached IDR 270,000–360,000 per planting cycle. The results of this program demonstrate that optimizing home garden land through ginger cultivation can significantly enhance household welfare and food security while promoting economic independence among rural communities.